(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Assess the nutritional status of ovarian cancer patients at National Cancer Hospital in 2024-2025. Materials and method: Cross-sectional descriptive study on 121 ovarian cancer patients from July 2024 to March 2025 at K Hospital. Results: The study on ovarian cancer patients showed that 9.1% were malnourished and 11.6% were overweight or obese based on Body Mass Index (BMI). According to the PG-SGA assessment, 43.8% of patients were at risk of mild to moderate malnutrition, and 9.1% were at risk of severe malnutrition. The rate of anemic patients was 38%, up to 42.1% of patients had symptoms of fatigue, 35.5% of patients had symptoms of anorexia, 32.2% had symptoms of early satiety and 24.8% had symptoms of dry mouth, in addition, symptoms of constipation, nausea, food taste, pain, mouth ulcers had rates of 19%; 13.2%; 12.4%; 12.4%; 9.1% respectively. Within a one-month period, 9.9% of patients lost 5–10% of their body weight, and 1.7% lost at least 10%. Over a six-month period, 15.7% of patients lost 5–10% of their body weight, and 6.6% experienced a weight loss of at least 10%. Conclusion: A significant proportion of ovarian cancer patients before surgery have nutritional problems such as anemia, weight loss, and malnutrition.